Thermal damage of conventional hard chromium coatings on 416 stainless steel. (November 2019) - Almotairi, Abdullah; Farhat, Zoheir; Warkentin, Andrew
Abstract: Hard chromium coatings have a wide range of application due to their resistance to corrosion and wear. In the present work, chromium was commercially electroplated on 416 stainless steel. Thermal damage of the chromium coatings was investigated as a function of heating temperature and cooling rate. Specimens were heated to various temperatures and then cooled down either by air cooling or water quenching. An optical microscope was employed to assess the damage due to heating. No thermally-induced cracks were observed for specimens heated up to 600 °C. At 800 °C and higher, thermally-induced cracks were observed and increased with increasing temperature. Cracks generated during heating were likely due to thermal expansion coefficient mismatch between the coating and the substrate. Heating was found to significantly alter the residual stresses state in the coating. Residual stress increased when heated to 600 °C and dropped at 1000 °C. Spherical indentations were employed to evaluation the effects of heating on the mechanical damage of the coatings. Ring, cone, surface radial and radial bend cracks were observed on as-deposited and heated specimens up to 600 °C. Specimen heated up to 800 °C showed partially developed ring and radial bend cracks, while specimen heated up to 1000 °C displayed no indentation related cracks. Highlights: Beyond 600 °C, thermally-induced cracks were observed on the coatings. Thermal cracks were likely caused by thermal expansion coefficient mismatch. Coating hardness substantially dropped beyond 600 °C. Heating increases residual stresses in coatings and thermal cracks release stresses. Thermal cracks changed mechanical response of coatings to indentation loading.